RANCANG BANGUN SISTEM PRESENSI KULIAH MENGGUNAKAN QRCODE BERBASIS ESP32CAM - Dedi Ary Prasetya; Muhammad Riska Wibowo (Inisiasi, 2023)
Rapid Response Codes are a kind of digital bar code that are becoming more and more popular since they can store a lot of data fast and in big quantities. This research aims to design a device for collecting attendance data using QR codes. This QR code contains information about the user's identity and location when used. We may determine the user's distance from the designated area using this location data. This location information is used to find out how far the user is from the area we have set.The presence method used  the ESP Cam device to scan a QR code from the user which contains information on student identification number, date and location (latitude and longitude).Before scanning the QR code, users must confirm via the Telegram application which has been prepared in advance to carry out the attendance process at each class session.Ifthe information matches that is stored in the database and the user's location is still within the radius of the reader device, the user's identity data is then uploaded to the online presence system.After the hardware and software have been prepared, it continues with testing on Electrical Engineering students at Muhammadiyah University of Surakarta as attendance at the Electrical Engineering Laboratory.Scanning this QR code takes an average reading time of 3.5 seconds with the fastest estimated time being 3 seconds and the longest 5 seconds.